Data privacy management, autonomous spontaneous security, and security assurance : 10th International Workshop, DPM 2015 and 4th International Workshop, QASA 2015, Vienna, Austria, September 21-22, 2015. Revised selected papers /: 10th International Workshop, DPM 2015 and 4th International Workshop, QASA 2015, Vienna, Austria, September 21-22, 2015. Revised selected papers. (2016) - Unknown
No abstract available